"INNOVATIONS IN EDUCATION DRIVEN BY ARTIFICIAL LEARNING TECHNOLOGIES ARE TRANSFORMING TRADITIONAL TEACHING METHODS AND ENHANCING PERSONALIZED LEARNING EXPERIENCES." (Modern education and development, 2025)
This article explores innovations in education, including technological advancements, personalized learning, e-learning, virtual and augmented reality applications, and their impact on modern educational environments. It highlights benefits, challenges, and future trends in education.